2015
DOI: 10.1590/1414-431x20144043
|View full text |Cite
|
Sign up to set email alerts
|

Association between anaerobic components of the maximal accumulated oxygen deficit and 30-second Wingate test

Abstract: The purpose of this study was to analyze the relationship between the anaerobic components of the maximal accumulated oxygen deficit (MAOD) and of the 30-second Wingate anaerobic test (30-WAnT). Nine male physical education students performed: a) a maximal incremental exercise test; b) a supramaximal constant workload test to determine the anaerobic components of the MAOD; and c) a 30-WAnT to measure the peak power (PP) and mean power (MP). The fast component of the excess post-exercise oxygen consumption and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 30 publications
4
46
1
1
Order By: Relevance
“…Therefore, the energy metabolism required to resynthesize lactic acid *Correspondence: fumiya.tanji@jpnsport.go.jp is significant during an 800m run. It is therefore considered that middle-distance runners have a high anaerobic energy metabolism and lactic acid resynthesis capacity, and AOD per 1 mM of ΔbLa in such runners would be different from data obtained using the values in previous studies [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Therefore, the energy metabolism required to resynthesize lactic acid *Correspondence: fumiya.tanji@jpnsport.go.jp is significant during an 800m run. It is therefore considered that middle-distance runners have a high anaerobic energy metabolism and lactic acid resynthesis capacity, and AOD per 1 mM of ΔbLa in such runners would be different from data obtained using the values in previous studies [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 83%
“…The AOD per 1 mM of ΔbLa has been considered to be 3.0 mLO2 · kg −1 · mM −1 by many researchers [6][7][8][9] . However, our study showed that the value was 19% higher, which suggested that use of the conventional coefficient underestimates research results obtained during supramaximal running of competitive athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation between bLa and anaerobic energy metabolism can be observed since bLa is increased when an anaerobic energy metabolism is recruited. 34) di Prampero et al 22) and other researchers 20,23,35,36) have calculated anaerobic energy production as 3.0 mLO2·kg −1 per 1 mmol·L −1 blood lactate accumulation; this method of calculation was used in the present study. Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Resting and peak blood lactate were recorded. Lactic anaerobic contribution was calculated by multiplying the ΔBL Peak-Resting by 3 as previously described using this estimation method in human subjects, 26,[28][29][30][31] and horses. 32 Calculated contributions (mL) were then converted into kJ (1 L O 2 = 20.92 kJ)…”
Section: Peak Exercise Testmentioning
confidence: 99%